Heart rate variability and inflammatory markers in neonates with hypoxic‐ischemic encephalopathy. Issue 15 (8th August 2019) - Yasova Barbeau, Daphna; Krueger, Charlene; Huene, Melissa; Copenhaver, Nicole; Bennett, Jeffrey; Weaver, Michael; Weiss, Michael D.
Abstract: To examine heart rate variability (HRV) and inflammatory markers as predictors for neurological injury in neonates undergoing therapeutic hypothermia for hypoxic‐ischemic encephalopathy (HIE). We hypothesized that HRV would differentiate between infants with no/mild injury and infants with moderate/severe injury observed on MRI. Because HRV can be associated with the inflammatory cascade, cytokine concentrations were compared with the severity of brain injury indicated by MRI. Further, we studied the effect of temperature, sex, and mechanical ventilation on HRV. HRV was prospectively collected on neonates with HIE using spectral analysis for low and high frequency components (n = 16). A subset (n = 10) of neonates had serum available for inflammatory cytokine analysis obtained during cooling. Neonates were stratified into no/mild or moderate/severe injury based on MRI obtained after rewarming. Differences in HRV were identified; lower low frequency power predicted more injury on MRI. Additionally, in neonates with HIE after cooling procedure, HRV differed by gender. Elevated RANTES (CCL5) and decreased GM‐CSF (Granulocyte‐macrophage colony‐stimulating factor) at 96 hours predicted less severe injury. In this small study, HRV differs between no/mild and moderate/severe injury in neonates with HIE. With further study, this may aid the clinician in real‐time decision making. HRV differs by gender. Finally, inflammatory biomarkers may help elucidate the pathophysiology of HIE. Abstract : Heart rate variability and inflammatory biomarkers are related to the degree of injury in hypoxic‐ischemic encephalopathy. This is the first study to evaluate infant sex, pressor use and mechanical ventilation when evaluating heart rate variability.